Scrum Effectiveness Measurement in Human Resources Technology Product at Telecommunication Company - Kurniawan, Yudi Candra (Journal of Informatics and Communication Technology (JICT), 2023)
Information technology currently sues the release of application become faster to fulfill market demand. The term application has become an ordinary thing to be used daily to support various kinds of work activities. Agile software development has become a new standard to catch up stakeholder needs that are growing faster and tending to change. One of agile practices, Scrum, is the methods used by Human Resources Technology (HR Tech) product. However, since HR Tech was established by using Scrum, measurement needs to be done to understand its effectiveness. Measurement use knowledge area defined in PMBOK 6 and mapped to agile-scrum process as the baseline to find out the effectiveness. Research was done by spreading questionnaires to the internal team of HR Team. The supporting data used internal company report. Furthermore, the research was processed by using validity and reliability to evaluate scrum process inside the product. The results show the top three knowledge areas need to be concerned to increase scrum effectiveness, there are communication, schedule, and quality. According to the knowledge areas which HR Tech need to be improved, future research should be done to demonstrate the proposed recommendations are appropriate with the case study.